Justice et agentivité distribuée chez les Mixe de Oaxaca (Mexique) - Perig Pitrou (Ateliers d'Anthropologie)
Through the study of various types of ritual speech uttered by judicial authorities during their service in a Mixe Indian village community, the aim of this article is to understand how the different kinds of agency attributed to non-human agents combine with human agency within a hierarchical judicial institution. Non-human entities are solicited to protect and “send ideas”, as well as participate in deliberative processes, something that leads one to consider how responsibility is attributed when decisions taken create new conflicts within a village.